Dampak Strategi Peningkatan Kualitas Lulusan SMK Negeri 1 Purwodadi Melalui Uji Sertifikasi Kompetensi - Suko Lisnanto; Nurkolis Nurkolis; Rosalina Br. Ginting (Cetta: Jurnal Ilmu Pendidikan, 2026)
This research aims to analyze strategies for improving the quality of graduates of SMK Negeri 1 Purwodadi through the implementation of the Professional Certification Institute (LSP) Competency Certification Test which is integrated with Teaching Factory learning and its impact on graduate output. The research was conducted using a qualitative approach with a descriptive type. Data collection techniques include observation, in-depth interviews, and documentation studies involving school principals, deputy principals for curriculum, LSP heads, productive teachers, and students. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions, by testing the validity of the data using triangulation of sources and techniques. The research results show that the strategy to improve the quality of graduates is carried out through the implementation of the Competency Certification Test which is integrated with teaching factory learning. The integration of the Professional Certification Institute Competency Certification Test with Teaching Factory learning has had a positive impact on graduate output, which is demonstrated by increased technical competence, work readiness, self-confidence, and graduate competitiveness in the world of work and industry. The conclusion of this research shows that the integration of the Competency Certification Test through the Professional Certification Institute with Teaching Factory learning is an effective strategy in improving the quality of output of graduates of SMK Negeri 1 Purwodadi. This research shows that the Professional Certification Institute Competency Certification Test is not only a tool for final evaluation of student competency, but also an integrated strategy for improving the quality of graduates that is integrated with the Teaching Factory, so this research shows that competency certification acts as a bridge for recognition by industry and higher education which expands the concept of quality of vocational school graduates from just technical competency to recognized and competitive competency.